2016
DOI: 10.5799/ahinjs.01.2016.02.0587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Pain and Foot Functions in Women with Hallux valgus deformities

Abstract: Objectives: The aim of this study was to investigate whether deformity affects pain and associated functional status in women with hallux valgus (HV). Methods:The study included 27 women (mean age: 40.5±10.3 years) diagnosed with HV and with a deformity level of two or more as determined using the Manchester scale. Demographic data of the participants were recorded. In addition, Visual Analog Scale (VAS) was used to determine the intensity of pain during walking. To determine the function affected by pain and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 19 publications
(35 reference statements)
0
5
0
Order By: Relevance
“…High heels have been proved to be one of the extrinsic factors that cause HV formation 7,13 as well as increasing its severity. 8,12 Wearing high heels elevates the pressure on the first metatarsal, which will eventually lead to HV formation, 13 which is an argument supported by Nguyen et al, 18 whose study reported that women wearing high heels 2 in. or more as the main shoes at the age of 20-64 years have 20% increased incidence of HV compared with those who do not.…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…High heels have been proved to be one of the extrinsic factors that cause HV formation 7,13 as well as increasing its severity. 8,12 Wearing high heels elevates the pressure on the first metatarsal, which will eventually lead to HV formation, 13 which is an argument supported by Nguyen et al, 18 whose study reported that women wearing high heels 2 in. or more as the main shoes at the age of 20-64 years have 20% increased incidence of HV compared with those who do not.…”
Section: Discussionmentioning
confidence: 91%
“…10 Most studies found that this condition appeared mostly in women, especially the ones who wore high heels shoes with a narrow toe box. 8,11…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations